2018
DOI: 10.5604/01.3001.0012.1270
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age on the body posture of women

Abstract: Introduction and aim of the study: The body posture, which is one of the determinants of health and functional efficiency, changes depending on gender, age and psychophysical condition. Defining a pattern of correct posture is extremely difficult as it is a highly individualised feature. The aim of this paper was to compare the body posture of women in three periods of ontogenesis: girls in puberty, young adult women and women in the geriatric age. Material and methods: 150 women were examined: 50 12-year-old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In our research, a higher incidence of hyperlordosis in female than male students was found. A study by Jankowicz-Szymańska et al [ 52 ] demonstrated that hyperlordosis is characteristic for young female students, while hypolordosis is characteristic for older women. In general, an increase in thoracic kyphosis causes lumbar hyperlordosis to maintain sagittal balance [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our research, a higher incidence of hyperlordosis in female than male students was found. A study by Jankowicz-Szymańska et al [ 52 ] demonstrated that hyperlordosis is characteristic for young female students, while hypolordosis is characteristic for older women. In general, an increase in thoracic kyphosis causes lumbar hyperlordosis to maintain sagittal balance [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, most students with neutral lordosis were found in Q4 (N = 21; 25%). In some studies [62,79], hyperlordosis was found to be a more characteristic of young female students, whereas hyperkyphosis was more commonly in male students. In our study of 19 hyperlordotic students, 17 of them were female and 22 of 49 hyperkyphotic students were male, which is consistent with these studies.…”
Section: Association Of Pa and Sedentary Behavior (Time Spent Sitting...mentioning
confidence: 99%
“…Moreover, prolonged sitting is associated with poorer posture [62] and, subsequently, with imbalanced trunk muscles and abnormal spinal curvatures. It is known that an increase in thoracic kyphosis causes lumbar hyperlordosis to maintain sagittal balance [79]. This happens because fatigue-induced reduction in active muscle stiffness increases antagonistic co-contraction to maintain stability, resulting in increased spinal compression with fatigue [80].…”
Section: Association Of Pa and Sedentary Behavior (Time Spent Sitting...mentioning
confidence: 99%